N-Propionylmannosamine stimulates axonal elongation in a murine model of sciatic nerve injury - Christian Witzel; Werner Reutter; G Björn Stark; Georgios Koulaxouzidis (Neural Regeneration Research, 2015)
Increasing evidence indicates that sialic acid plays an important role during nerve regeneration. Sialic acids can be modified in vitro as well as in vivo using metabolic oligosaccharide engineering of the N-acyl side chain. N-Propionylmannosamine (ManNProp) increases neurite outgrowth and accelerates the reestablishment of functional synapses in vitro. We investigated the influence of systemic ManNProp application using a specific in vivo mouse model. Using mice expressing axonal fluorescent proteins, we quantified the extension of regenerating axons, the number of regenerating axons, the number of arborising axons and the number of branches per axon 5 days after injury. Sciatic nerves from non-expressing mice were grafted into those expressing yellow fluorescent protein. We began a twice-daily intraperitoneal application of either peracetylated ManNProp (200 mg/kg) or saline solution 5 days before injury, and continued it until nerve harvest (5 days after transection). ManNProp significantly increased the mean distance of axonal regeneration (2.49 mm vs. 1.53 mm; P < 0.005) and the number of arborizing axons (21% vs. 16% P = 0.008) 5 days after sciatic nerve grafting. ManNProp did not affect the number of regenerating axons or the number of branches per arborizing axon. The biochemical glycoengineering of the N-acyl side chain of sialic acid might be a promising approach for improving peripheral nerve regeneration.